129k views
25 votes
What is 2/3 (6x - 1/6) + 3x?​

User Kuo Jimmy
by
4.2k points

2 Answers

9 votes


= \tt (2)/(3) (6x - (1)/(6) ) + 3x


=\tt (2)/(3) * 6x - (2)/(3) * (1)/(6) + 3x


=\tt (2 * 6)/(3)x - (2 * 1)/(3 * 6) + 3x


= \tt (12)/(3) x - (2)/(18) + 3x


=\tt 4x - (2 / 2)/(18 / 2) + 3x


= \tt4 x- (1)/(9) + 3x


= \tt4x + 3x - (1)/(9)


\color{plum}= \tt\bold{7x - (1)/(9) }

Therefore,


\color{hotpink}\tt (2)/(3) (6x - (1)/(6) ) + 3x \color{plm}= \color{plum}\tt\bold{7x - (1)/(9) }

User Evers
by
4.9k points
4 votes

answer::

7x=-1/9!!!!!

User Fiddling Bits
by
4.9k points